Differential Effect of Viable Versus Necrotic Neutrophils on Mycobacterium tuberculosis Growth and Cytokine Induction in Whole Blood - Lowe, David M.; Demaret, Julie; Bangani, Nonzwakazi; Nakiwala, Justine K.; Goliath, Rene; Wilkinson, Katalin A.; Wilkinson, Robert J.; Martineau, Adrian R. (Frontiers in Immunology, 2018)
Neutrophils exert both positive and negative influences on the host response to tuberculosis, but the mechanisms by which these differential effects are mediated are unknown. We studied the impact of live and dead neutrophils on the control of M. tuberculosis using a whole blood bioluminescence-based assay, and assayed supernatant cytokine concentrations using Luminex™ technology and ELISA. CD15+ granulocyte depletion from blood prior to infection with M. tuberculosis-lux impaired control of mycobacteria by 96 hours, with a greater effect than depletion of CD4+, CD8+ or CD14+ cells (p<0.001). Augmentation of blood with viable granulocytes significantly improved control of mycobacteria by 96 hours (p=0.001), but augmentation with necrotic granulocytes had the opposite effect (p=0.01),. Both augmentations decreased supernatant concentrations of TNF and IL-12 p40/p70, but necrotic granulocyte augmentation also increased concentrations of IL-10, G-CSF, GM-CSF and CCL2. Necrotic neutrophil augmentation reduced phagocytosis of FITC-labelled M.bovis-BCG by all phagocytes whereas viable neutrophil augmentation specifically reduced early uptake by CD14+ cells. The immunosuppressive effect of dead neutrophils required necrotic debris rather than supernatant. We conclude that viable neutrophils enhance control of M. tuberculosis in blood, but necrotic neutrophils have the opposite effect – the latter associated with induction of IL-10, growth factors and chemoattractants. Our findings suggest a mechanism by which necrotic neutrophils may exert detrimental effects on the host response in active tuberculosis.